2016
DOI: 10.1016/j.carj.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of the Radiographic Appearances of the Calcium Sulfate-Calcium Phosphate Synthetic Bone Graft Composite following Resection of Bone Tumors: A Follow-up Study of Postoperative Appearances

Abstract: Our study suggests a characteristic time and volume related radiographic pattern of resorption and new bone ingrowth with the CaSO4/CaPO4 synthetic graft. Findings that deviate from this pattern may represent complication and warrant additional follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Kotnis, et al described chronological radiographic appearance of a calcium sulphate-calcium phosphate matrix mixed with beta-tricalcium phosphate granules following bone tumour resection in 11 patients 41. Their findings showed some similarities to our own: resorption commenced peripherally with gradual inward progression; complete resorption of the BGS was seen at six months 41,42. Since the radiographic appearance of BGS are variable and can lead to confusion with recurrent or residual disease 43, it is important to understand the time-dependant changes which are seen during follow-up.…”
Section: Discussionsupporting
confidence: 70%
“…Kotnis, et al described chronological radiographic appearance of a calcium sulphate-calcium phosphate matrix mixed with beta-tricalcium phosphate granules following bone tumour resection in 11 patients 41. Their findings showed some similarities to our own: resorption commenced peripherally with gradual inward progression; complete resorption of the BGS was seen at six months 41,42. Since the radiographic appearance of BGS are variable and can lead to confusion with recurrent or residual disease 43, it is important to understand the time-dependant changes which are seen during follow-up.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, due to the introduction of CP, the mechanical strength of the composite is superior to CS and autogenous cancellous bone (17). Both animal studies and clinical studies have demonstrated the satisfactory osteogenesis and antibiotic loading effect of CS/CP composites (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this pilot study was to develop a large animal model that would replicate a common clinical bone defect scenario as closely as possible and would also allow detailed analysis of the bone healing response to bone defect filling with a BGS in comparison to cancellous allograft or no filling at all. Since the resorption patterns of ceramic BGS are challenging to interpret and its transformation into bone are difficult to substantiate in clinical practice , we anticipated that the analysis of multiple different imaging modalities in correlation and accordance with histological findings would help to replicate, clarify and better understand clinical observations in humans.…”
mentioning
confidence: 99%